A COMPARISON OF THE SPATIAL AND THE KINEMATICS DISTRIBUTION OF MILKY WAY'S WARP BETWEEN OBSERVATIONAL AND SIMULATION DATA - Maulana Nurhidayat, Rizky
The disk components of Milky Way develop warp, both in HI gas and stellar disk. The origin of the galactic warp is still debatable. Besides, the asym- metrical deviation in the Northern Warp and the Southern Warp shows the intricate pattern. In this study, we analyse the spatial and kinematics distribution of the Milky Way's warp from Gaia DR2, LAMOST DR5, RAVE DR5, and GALAH DR2 by comparing it with the warp from simulation data, GALAXIA and AURIGAIA. We use OB and RGB stars as the tracers. We do a parameter tting using a No U-turn Sampler (NUTS) algorithm. To dierentiate the data point in the unwarped group and warped group, we use a logistic function. The results show that the complexity of the warp pattern developing in OB stars. We estimate the onset radius of the warp is on Rw = 12 ???? 13 kpc and the Line-of-Node (LoN) is in about ????8 < w < 8. The propagating wave, which is not concentric, shows the eects of spiral arms in warp evolution. The warp in RGB stars shows the asymmetrical deviation from its value of warp parameters. The Northern Warp starts at Rw = 10:51 kpc, whereas the Southern Warp starts at Rw = 10:46 kpc. The amplitude, power-law value, and LoN of the warp in the Northern Warp are w = 0:21, w = 1:79, dan w = 0:90, respectively. The warp parameters from the Southern warp show a little bit dierent. They are w = 0:18, w = 1:66, dan w = ????5:94. AURIGAIA could produce a warped galaxy, both in spatial and kinematics dis- tribution. But, not in GALAXIA. The warped galaxy in GALAXIA simulation could only be seen in spatial distribution. The tting of the warped galaxy in GALAXIA can lead us to a benchmark model for our proposed tting methods. The interaction between the host galaxy and its satellites in AURIGAIA shows that the origin of the Milky Way's warp is the tidal interaction with less massive satellites as the primary mechanism. The dierent deviation in OB and RGB shows the high degree of complexity of the warp evolution.